Tot (Training Of Trainer) Parameter Test Atlet Panjat Tebing PPLP DIY 2021 - Taryatman; Suharjana; Anang Sulistya; Dhedhy Yuliawan; Puspodari; Wing Prasetya Kurniawan; Nur Ahmad Muharram (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of holding this parameter test is to equip DIY Climbing PPLP trainers and their staff to know the physical condition of the DIY Climbing PPLP athletes so that the training program can be right on target. In addition, parameter tests are also used to evaluate the progress of training towards achievement in competitions in each championship. This parameter test also has benefits, namely to determine the method of preparing parameter tests and preparation of test implementation guidelines, or SOPs so that the parameter tests carried out in the field have valid and reliable test prerequisites, and have the same interpretation throughout Indonesia, especially in the Climbing Sports Branch. Cliff. The method here uses the field practice method through DIY Climbing PPLP athletes to carry out a series of parameter tests in sports that are in accordance with the needs of the physical components of rock climbing athletes. Athletes are asked to carry out a series of tests in accordance with a predetermined SOP. The result of this parameter test is that PPLP DIY Climbing athletes in 2021 have physical conditions in either category or in good norms in each form of test that is directed at the physical condition of Climbing athletes. Keyword: parameter test, DIY, climbing.